Интеллектуальный анализ данных - Гисцев, А. Ю.; Заворотна, М. Г. (ХНУРЕ, 2019)
Data mining is the selection of information in large amounts of raw data. These data can be different types of materials: photos, graphics, sounds, experimental data, etc. Data mining uses well-researched statistical principles to highlight patterns in the data. By applying data mining algorithms to your data, you can predict trends, highlight patterns, create rules and recommendations, analyze the sequence of events in complex datasets, and discover new dependencies. Patterns and trends can be combined, with the resulting mining models. The process of intellectual analysis consists of certain stages, which include comparisons, classifications, synthesis, repetition, typing, abstraction. In turn, this whole process is directly related to the decision-making process.
Keywords: аналіз даних; засоби інтелектуального аналізу; великі дані; обробка даних